2017
DOI: 10.5539/ijel.v7n5p84
|View full text |Cite
|
Sign up to set email alerts
|

The L2 Motivational Self System and Religious Interest among Saudi Military Cadets: A Structural Equation Modelling Approach

Abstract: This study surveyed the English language learning motivation of 384 Saudi military cadets. The researcher applied structural equation modelling to analyse how a set of motivational factors interact in shaping the motivation to learn English of this under-researched context. The study found that the language learning effort was determined by the students’ attitudes towards the language learning process as well as their Ought-to L2 Self. However, the Ideal L2 Self contributed to the language learning effort indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Therefore, scholars such as Kormos et al (2011) and Taguchi et al (2009) suggest that the OL2S is likely to have a more salient role in Arab and Asian contexts, where the expectations of students' parents can be powerful motivators. The impact of the OL2S on the learning effort of L2 Saudi students was salient in Alqahtani's (2017a) study. In addition, it has been found in a number of studies, such as Csizér and Kormos (2009), Kormos et al (2011), andTaguchi et al (2009), that the OL2S was directly influenced by parental encouragement, which led Csizér and Kormos (2008a) to conclude that "the OL2S is entirely socially constructed" (p. 177).…”
Section: The L2mssmentioning
confidence: 88%
“…Therefore, scholars such as Kormos et al (2011) and Taguchi et al (2009) suggest that the OL2S is likely to have a more salient role in Arab and Asian contexts, where the expectations of students' parents can be powerful motivators. The impact of the OL2S on the learning effort of L2 Saudi students was salient in Alqahtani's (2017a) study. In addition, it has been found in a number of studies, such as Csizér and Kormos (2009), Kormos et al (2011), andTaguchi et al (2009), that the OL2S was directly influenced by parental encouragement, which led Csizér and Kormos (2008a) to conclude that "the OL2S is entirely socially constructed" (p. 177).…”
Section: The L2mssmentioning
confidence: 88%
“…In addition, they maintain their motivation by reminding them of their goals to master their language learning goals. Affirming the benefits of mastering the target language seems beneficial for students (Alqahtani, 2017). In this sense, teachers can encourage students to remember their language learning goals as well as the benefits of language mastery such as getting better jobs or traveling abroad.…”
Section: Discussionmentioning
confidence: 99%
“…In this category, we found two research studies. The first one was Nomnian & Arphattananon (2018) and the second being Alqahtani (2017). Nomnian & Arphattananon (2018) in their qualitative research with six government primary schools administrators in Thailand found five essential key competencies leading to achieve success in English language teaching and learning.…”
Section: C) Family/parental Engagementmentioning
confidence: 99%
“…The research highlighted that these factors are entwined in the educational networks that need permanent and shared contributions from all important stakeholders encouraging learners towards English language learning success. Alqahtani (2017) in his quantitative study underlined that the influence of students' parents was salient as parental encouragement promoted their ought-to L2 self-FAMILY AND ENGLISH LANGUAGE LEARNING motivation in addition to their attitudes about language learning. The research study points out the considerable impact of parents on their children in this research context of Saudi Arabia which, according to the researcher, is a conservative and collective society.…”
Section: C) Family/parental Engagementmentioning
confidence: 99%